Dominansi Pengaruh Literasi Keuangan, Kecerdasan Emosional, Financial Self-Efficacy, dan Pembelajaran Keuangan di Kampus terhadap Perilaku Pengelolaan Keuangan Mahasiswa (Studi Kasus Mahasiswa STIE Indonesia Jakarta) - Nelli Novyarni; Nabilah Amanda; Reni Harni; Kartijo Kartijo (Jurnal EMT KITA, 2026)
This study aims to analyze the influence of financial literacy, emotional intelligence, financial self-efficacy, and campus financial learning on the financial management behavior of students’ at STIE Indonesia Jakarta in the 2021 and 2022 Academic Years. This type of research is quantitative research with an associative approach. The data used is primary data obtained by distributing questionnaires to respondents. The sample in this study amounted to 110 students, consisting of students of the 2021 and 2022 intakes of the S-1 Accounting and S-1 Management study programs, who were selected using a non-probability sampling technique with a purposive sampling method. The research instrument consists of 24 questionnaire items arranged based on indicators of each variable, and distributed in the form of Google Form. Data analysis was carried out using SmartPLS version 4.0, including the stages of evaluating the measurement model, The R-square value of 0.677 indicates that the independent variables in the model explain 67.7% of the variance in the dependent variable. The remaining 32.3% is explained by factors outside the model. Therefore, the results of this study indicate that financial literacy, emotional intelligence, financial self-efficacy, and financial learning on campus significantly influence the financial management behavior of students at STIE Indonesia Jakarta.